Physiological, metabolic and practical considerations for training swimmers - Bonen, A.; Kemp, N. H. (Research Papers in Physical Education, 1977)
On some physiological and metabolic facts in swimming. Implication: As a general rule for training swimmers, the shorter the distance the fewer the number of repeats. Research has repeatedly shown that the rate of physiological adaptation occurs primarily in response to the intensity of effort rather than the total amount of effort. Therefore, the principle concept for swim training is effective yardage.